The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1088/0256-307x/28/9/092503
|View full text |Cite
|
Sign up to set email alerts
|

Centrality in Relativistic Nuclear Collisions and the Random Matrix Approach

Abstract: Using the random matrix approach, results for nearest-neighbor distributions obtained from experimental data on 12 𝐢 + 12 𝐢 collisions at 4.2 𝐴 GeV/𝑐 and simulations produced with the aid of an ultra-relativistic quantum molecular dynamics model are studied. Comparison reveals that the observed changes in the nearest-neighbor distributions for different multiplicities can be associated with the onset of a region of central collisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Indeed, one can find a good agreement between the results obtained in this way and a standard analysis based on the method of effective mass spectra and two-pair correlation function often used in high energy physics [18]. The purpose of the present review is to discuss a novel criterion for the centrality of collision, using a rigorous mathematical framework of the RMT [18][19][20][21][22]. Section 2 briefly reviews how to detect the manifestation of correlations with the aid of nearest-neighbor spacing energy distribution (NND) from the data obtained in light nuclei collisions in Dubna Experiments.…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…Indeed, one can find a good agreement between the results obtained in this way and a standard analysis based on the method of effective mass spectra and two-pair correlation function often used in high energy physics [18]. The purpose of the present review is to discuss a novel criterion for the centrality of collision, using a rigorous mathematical framework of the RMT [18][19][20][21][22]. Section 2 briefly reviews how to detect the manifestation of correlations with the aid of nearest-neighbor spacing energy distribution (NND) from the data obtained in light nuclei collisions in Dubna Experiments.…”
Section: Introductionmentioning
confidence: 55%
“…Evidently, the absence of an unambiguous criterion for the centrality may significantly affect the interpretation of experimental results and, therefore, hide a true signal on the onset of a new phase of the hadronic matter. In a preliminary report [15] it is suggested that tools from Random Matrix Theory (RMT) [16][17][18][19][20][21][22] might be useful in illuminating the presence of correlations in the spectral (momentum) distribution of secondary particles produced in nucleusnucleus collisions at high energy [18][19][20][21][22]. It is noteworthy that during the last twenty years the RMT grew into the powerful new statistical theory of fluctuations in a variety of physical problems [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations